Investimento direto e internacionalizaç\~ao de empresas brasileiros no período recente - Célio Hiratuka; Fernando Sarti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This article evaluated the recent changes in the profile and determinants of Brazilian firm's internationalization process. In the '90s, it was not intense, but highly concentrated on a few large domestic companies, and resulted from both strategies: to compensate the low dynamism of the domestic market and/or to circumvent protectionist barriers to their exports. From mid 2000s, the internationalization strategy covered a larger broad of sectors (industry and services) and companies, including midsize firm, specially the ones with regional participation. Nonetheless, the process was more intensive in the commodities sectors (oil, mining, steel, pulp and paper and food) and services (engineering and construction) with global insertion. This fact reflects the specialization pattern of the productive structure and the largest competitiveness of these sectors. The improvement in financial indicators and financing conditions were decisive to support a new phase of internationalization of Brazilian domestic companies. The higher profitability contributed to improve their capability of self-financing as well as leveraging. Also decisive was the BNDES performance in lending and /or facilitating companies' capitalization, mainly to facilitate the mergers and acquisitions (M&A). These movements explicit a change the Brazilian companies internationalization strategies, which turned to be more active.
Keywords: F23; F15; L1; 330; Multinationales Unternehmen; Auslandsinvestition; Brasilien